Oil prices, gasoline prices and inflation expectations: A new model and new facts - Lutz Kilian; Xiaoqing Zhou (Goethe University Frankfurt, Center for Financial Studies (CFS), 2020)
The conventional wisdom that inflation expectations respond to the level of the price of oil (or the price of gasoline) is based on testing the null hypothesis of a zero slope coefficient in a static single-equation regression model fit to aggregate data. Given that the regressor in this model is not stationary, the null distribution of the t-test statistic is nonstandard, invalidating the use of the normal approximation. Once the critical values are adjusted, these regressions provide no support for the conventional wisdom. Using a new structural vector regression model, however, we demonstrate that gasoline price shocks may indeed drive one-year household inflation expectations. The model shows that there have been several such episodes since 1990. In particular, the rise in household inflation expectations between 2009 and 2013 is almost entirely explained by a large increase in gasoline prices. However, on average, gasoline price shocks account for only 39% of the variation in household inflation expectations since 1981.
urn:nbn:de:hebis:30:3-558254
Keywords: E31; E52; Q43; 330; inflation; expectations; anchor; missing disinflation; oil price; gasoline price; household survey